Drivers and patterns of microbial community assembly in a Lyme disease vector. Issue 13 (13th June 2019) - Couper, Lisa I.; Kwan, Jessica Y.; Ma, Joyce; Swei, Andrea
Abstract: Vector‐borne diseases constitute a major global health burden and are increasing in geographic range and prevalence. Mounting evidence has demonstrated that the vector microbiome can impact pathogen dynamics, making the microbiome a focal point in vector‐borne disease ecology. However, efforts to generalize preliminary findings across studies and systems and translate these findings into disease control strategies are hindered by a lack of fundamental understanding of the processes shaping the vector microbiome and the interactions therein. Here, we use 16S rRNA sequencing and apply a community ecology framework to analyze microbiome community assembly and interactions in Ixodes pacificus, the Lyme disease vector in the western United States. We find that vertical transmission routes drive population‐level patterns in I. pacificus microbial diversity and composition, but that microbial function and overall abundance do not vary over time or between clutches. Further, we find that the I. pacificus microbiome is not strongly structured based on competition but assembles nonrandomly, potentially due to vector‐specific filtering processes which largely eliminate all but the dominant endosymbiont, Rickettsia . At the scale of the individual I. pacificus, we find support for a highly limited internal microbial community, and hypothesize that the tick endosymbiont may be the most important component of the vector microbiome in influencing pathogen dynamics. Abstract : Vector microbiomes can play a critical role in pathogen transmission; however, the processes responsible for shaping the vector microbiome remain largely unknown. This study employs a community ecology framework to investigate community assembly of the tick microbiome. Both environmental and vertical transmission routes shaped population‐level patterns of the tick microbiome, but individual ticks harbored depauperate microbial communities.